Bioactivity of Spagneticola trilobata Flower Extract against Fall Army Worm Spodoptera frugiperda J. E. Smith - R. Arif Malik Ramadhan; Efrin Firmansyah (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2020)
Fall armyworm (Spodoptera frugiperda) is a new pest that attacks maize plantations in Indonesia. Local farmers generally use synthetic pesticides to control the pest that can cause environmental and health problems, and in the future will trigger resistance of the pest to insecticide. This study aimed to determine the potential of Sphagneticola trilobata flower extracts on mortality, larval weight, weight of food consumption, and inhibition of feeding activity in S. frugiperda larvae. The research method is completely randomized design with 6 treatments and 3 replications. The treatments consisted of control treatments, S. trilobata flower extract 1%, 2%, 3%, 4%, and 5%. Mortality, larval weights and food consumption data were analyzed using analysis of variance. The results showed that the S. trilobata flower extract at the highest concentration of 5% resulted in larval mortality of 72.22. These results indicated that the S. trilobata flower extract was not effective against S. frugiperda. However, S. trilobata extract can influence other biological aspects, such as feeding activity and growth of S. frugiperda larvae. Tratment of 5% of S. trilobata extract resulted in weight of feed comsumption of 0.123 g with inhibition of feeding activity of 66.11%, and average weight of larvae of 0.048 g that were lower than control treatment.